Dispersal, landscape and travelling waves in cyclic vole populations. (17th November 2013) - Berthier, Karine; Piry, Sylvain; Cosson, Jean‐François; Giraudoux, Patrick; Foltête, Jean‐Christophe; Defaut, Régis; Truchetet, Denis; Lambin, Xavier; Liebhold, Andrew
Abstract Travelling waves (TW) are among the most striking ecological phenomena emerging in oscillating populations. Despite much theory, understanding how real‐world TW arise remains a challenge for ecology. Herein, we analyse 16‐year time series of cyclic vole populations collected at 314 localities covering 2500 km² in France. We found evidence for a linear front TW spreading at a speed of 7.4 km year−1 along a north‐west/south‐east direction and radiating away from a major landscape discontinuity as predicted by recent theory. The spatial signature of vole dispersal was assessed using genetic data collected at 14 localities. Both data sets were handled using similar autocorrelation approaches. Our results revealed a remarkable congruence of the spatial extent and direction of anisotropy of both demographic and genetic structures. Our results constitute the first empirical evidence that effective dispersal is limited in the direction of TW while most of the individual exchanges occur along the wave front.